Theorizing varieties of capitalism: Economics and the fallacy that "There is no alternative (TINA)" - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2022)
The varieties of capitalism (VoCs) approach has the potential to transform economics. It implicitly emphasizes the plasticity of economies, whereby their character and outcomes are significantly a matter of choice. This paper augments VoCs theory to include a distinction between varieties and varietals of capitalism. Drawing on biology, varieties correspond to species and varietals correspond to sub-species. The paper proposes an analytical framework that unifies VoCs theory. It adds a mesoeconomics that links macroeconomics and microeconomics. That mesoeconomics concerns the institutions, behavioral norms, rules and regulations, and policies that characterize the economy and influence its performance. The mesoeconomic structure is described using the metaphor of a box, the six sides of which correspond to the major dimensions of capitalist economies. The design of the box is the product of societal and political choices, which places politics at the center of VoCs analysis. Policy space and policy lock-in are important concerns as they impact the choice set. The fact that economies inevitably involve choice means there is an inescapable normative question regarding what type of capitalism society will have.
Keywords: P0; P1; D2; 330; Varieties of capitalism; varietals of capitalism; mesoeconomics; globalization; policy space; policy lock-in